2019
DOI: 10.1002/elps.201800437
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and independent dielectrophoretic behavior of the head and tail of sperm and its potential for the safe sorting and isolation of rare spermatozoa

Abstract: Often, in semen samples with minute amounts of sperm, even the single spermatozoon required to fertilize an oocyte cannot be found in the ejaculate. This is primarily because currently, sperm is generally searched for manually under a microscope. In this study, dielectrophoresis (DEP) was investigated as an alternative automated technique for sorting sperm cells. Using a quadrupolar electrode array it was shown that the head and tail of the sperm had independent and unique crossover frequencies corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Hence, no intermediate equilibrium positions were obtained within the quadrupolar electrode array. In contrast, here we will demonstrate that if we engineer the Janus particle to have a large enough separation between its dielectric and metallic coated parts similar 2 to sperm cell [12], such intermediate equilibrium positions could be achieved. Such engineered Janus particle with controlled geometry and selective metallic coating is obtained using standard photolithography fabrication technique [13] (see supplementary materials for details of the particle fabrication).…”
mentioning
confidence: 71%
“…Hence, no intermediate equilibrium positions were obtained within the quadrupolar electrode array. In contrast, here we will demonstrate that if we engineer the Janus particle to have a large enough separation between its dielectric and metallic coated parts similar 2 to sperm cell [12], such intermediate equilibrium positions could be achieved. Such engineered Janus particle with controlled geometry and selective metallic coating is obtained using standard photolithography fabrication technique [13] (see supplementary materials for details of the particle fabrication).…”
mentioning
confidence: 71%
“…Electrophoresis was first used to separate X and Y-sperm around 40 years ago, this technique demonstrated the high efficiency of separation but was very toxic to sperm [36,37]. Electrophoresis use a uniform electric field, generated using direct current (DC), this technique uses high energy to move the cell and can be more lethal to the cells than dielectrophoresis [38,39]. Our study demonstrated that dielectrophoresis is safe for sperm in the proper buffer, the decrease in sperm quality was not affected by the electrical condition but the buffer choice.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then released by lowering the frequency incrementally and collected at an outlet port. Schucat et al 146 designed an electrode array in a microfluidic device to act as an automated platform for sperm cell separation. A quadrupolar electrode array was fabricated onto an indium tin oxide (ITO)-coated glass slide using photolithography and wetetching and a PDMS microchannel was utilized to examine the effects of different DEP forces on sperm cells.…”
Section: ■ Cell Separation Methodsmentioning
confidence: 99%